Pembelajaran Berbasis Masalah sebagai Strategi Inovatif untuk Meningkatkan Hasil Belajar Biologi pada Materi Keanekaragaman Hayati - Hironima Pridi; Sardina Ndukang; Aloysius Djalo; Hildegardis Missa (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Biology education, particularly in the topic of biodiversity, faces challenges in improving student learning outcomes. One effective approach is problem-based learning (PBL), which promotes active student involvement in solving real-world problems. This study examines the impact of PBL on Student Learning Outcomes in biodiversity at the high school level. A quasi-experimental design was conducted at SMA Negeri 5, involving two classes selected through purposive sampling: an experimental class using PBL and a control class taught using conventional methods. Learning outcomes were assessed via pretests, posttests, N-Gain analysis, and ANCOVA. The results showed a significant improvement in the experimental class. The average pretest score for the experimental class was 45.63, while the posttest score increased to 80.1, resulting in an N-Gain of 0.37 (moderate). In contrast, the control class had a pretest score of 45.31 and a posttest score of 75, with an N-Gain of 0.49. Despite the control class showing a slightly higher N-Gain, the PBL model was more effective in improving learning outcomes, with 93.75% of students in the experimental class achieving mastery compared to 65.63% in the control class. ANCOVA results revealed a p-score of 0.002, confirming that PBL significantly enhances student learning outcomes.